Catalytic transesterification of beta-ketoesters with zeolite H-FER under solvent free conditions - Chavan, Subhash P.; Pasupathy, K.; Shengule, S.; Shinde, V.; Anand, R. (Arkivoc, 2005)
Zeolite H-FER catalyzes the transesterification of beta-ketoesters with variety of alcohols under solvent-less condition in excellent yields. The catalyst can be reused without any loss of activity.
Keywords: ferrierite; transesterification; zeolite

Corrosion protective poly(o-toluldine) coatings on copper - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Corrosion Science, 2005)
This study examines the use of poly(o-toulidine) (POT) coatings for corrosion protection of copper (Cu) in an aqueous solution of 3% NaCl. The POT coatings were synthesized on Cu substrates under cyclic voltammetric conditions from an aqueous solution of sodium oxalate. The resulting, POT coatings were uniform, shiny and strongly adherent to the Cu substrates. These coatings were characterized by cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The ability of POT to serve as a corrosion protective coating for Cu was examined by potentiodynamic polarization measurements and CV. The results of this study clearly reveal that the POT acts as corrosion protective coating on Cu and reduces the corrosion rate of Cu almost by a factor of 40. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Electrochemical synthesis and corrosion protection properties of poly(o-toluidine) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Patil, P. P. (Journal of Applied Polymer Science, 2005)
Uniform and strongly adherent poly(o-toluidine) (POT) coatings have been synthesized on low carbon steel (LCS) substrates by electrochemical polymerization (ECP) of o-toluidine under cyclic voltammetric conditions from an aqueous sodium tartrate solution. Cyclic voltammetry (CV), UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) measurements, and scanning electron microscopy (SEM) were used to characterize these coatings, which indicates that the sodium tartrate is a suitable medium for the ECP of o-toluidine and it occurs without noticeable dissolution of LCS. Corrosion protection properties of the POT coatings were evaluated in aqueous 3% NaCl by the potentiodynamic polarization measurements and CV. The result of the potentiodynamic polarization demonstrates that the POT coating has ability to protect the LCS against corrosion. The corrosion potential was about 334 mV more positive in aqueous 3% NaCl for the POT-coated LCS than that of bare LCS and reduces the corrosion rate of LCS almost by a factor of 50. (c) 2005 Wiley Periodicals, Inc.
Keywords: conducting polymers; Corrosion resistant coatings; cyclic voltarnmetry; Electrochemical polymerization; FT-IR; Poly(o-toluidine); UV-vis spectroscopy

Poly(o-toluidine) coatings on copper: electrochemical synthesis from aqueous media - Shinde, V.; Mandale, A. B.; Patil, K. R.; Gaikwad, A. B.; Patil, P. P. (Surface & Coating Technology, 2006)
Poly(o-toluidine) (POT) coatings were synthesized on copper (Cu) by electrochemical polymerization of o-toluidine using aqueous sodium oxalate solution as supporting electrolyte. The resulting coatings were uniform, compact and strongly adherent to the Cu substrate. These coatings were characterized by using cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X-ray diffraction (XRD) measurements and X-ray photoelectron spectroscopy (XPS). The results of these studies reveal that the sodium oxalate is suitable supporting electrolyte for the electrochemical polymerization of o-toluidine on Cu substrate. It is found that the electrochemical polymerization of o-toluidine takes place after the passivation of the Cu substrate via formation of copper oxalate (CuC2O4, H2O) layer, which is confirmed by XRD and XPS. The optical absorption spectroscopy study reveals the exclusive formation of the pernigraniline base (PB) form of POT. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Conducting polymer coatings; Copper; Corrosion resistant coatings; cyclic voltammetry; poly(o-toluidine) coatings

Synthesis of corrosion inhibitive poly(2,5-dimethylaniline) coatings on low carbon steel - Shinde, V.; Sainkar, S. R.; Gangal, S. A.; Patil, P. P. (Journal of Materials Science, 2006)
An attempt has been made towards the synthesis of strongly adherent poly(2,5-dimethylaniline) coatings on low carbon steel substrates, with an objective of examining the possibility of using this polymer for corrosion protection of steel in chloride environment. In this work, the poly(2,5-dimethylaniline) coatings were synthesized by electrochemical polymerization of 2,5-dimethylaniline using sodium salicylate as a supporting electrolyte. The characterization of these coatings was carried out by cyclic voltammetry, UV-visible absorption spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy. The results of these characterizations indicate that the aqueous salicylate solution is a suitable medium for the electrochemical polymerization of 2,5-dimethylaniline to generate strongly adherent and smooth poly(2,5-dimethylaniline) coatings on low carbon steel substrates. The performance of poly(2,5-dimethylaniline) as protective coating against corrosion of low carbon steel in aqueous 3% NaCl was assessed by the open circuit potential and the potentiodynamic polarization measurements. The potentiodynamic polarization measurement reveals that the poly(2,5-dimethylaniline) coating increases the corrosion potential and reduces the corrosion rate of low carbon steel almost by a factor of 50. This study clearly ascertains that the poly(2,5-dimethylaniline) has outstanding capability to protect low carbon steel against corrosion in chloride environment. (c) 2006 Springer Science + Business Media, Inc.